Bystander macrophage apoptosis after Mycobacterium tuberculosis H37Ra infection. - O'Sullivan, Mary; Keane, Joseph; O'Leary, Seonadh (My University, 2008)
Human macrophages infected with Mycobacterium tuberculosis may undergo apoptosis. Macrophage apoptosis contributes to the innate immune response against M. tuberculosis by containing and limiting the growth of mycobacteria and also by depriving the bacillus of its niche cell. Apoptosis of infected macrophages is well documented; however, bystander apoptosis of uninfected macrophages has not been described in the setting of M. tuberculosis. We observed that uninfected human macrophages underwent significant bystander apoptosis 48 and 96 h after they came into contact with macrophages infected with avirulent M. tuberculosis. The bystander apoptosis was significantly greater than the background apoptosis observed in uninfected control cells cultured for the same length of time. There was no evidence of the involvement of tumor necrosis factor alpha, Fas, tumor necrosis factor-related apoptosis-inducing ligand, transforming growth factor beta, Toll-like receptor 2, or MyD88 in contact-mediated bystander apoptosis. This newly described phenomenon may further limit the spread of M. tuberculosis by eliminating the niche cells on which the bacillus relies.
PUBLISHED
Keywords: Cell Death; Mycobacterium tuberculosis; Apoptosis; Bystander apoptosis; Mycobacterium tuberculosis/physiology; Macrophages/microbiolog; Macrophages/microbiology; Mycobacterium tuberculosis/physiology; Cell Communication; Apoptosis